Problems of Cryptocurrency Development on Investor Protection from an Islamic Business Perspective - Suratno Suratno; Muhammad Jauharil Ma'arif (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
Cryptocurrencies have sparked intense debate within the global business and financial sectors. While promising substantial investment growth, they also present significant challenges, particularly concerning investor protection. In the context of Islamic business, the emergence of cryptocurrencies raises profound questions regarding compliance with Sharia principles and safeguarding investor interests. This article aims to scrutinize these issues from an Islamic business perspective, focusing on investor protection. Through a synthesis of literature and conceptual analysis, this study identifies several critical concerns. Firstly, it assesses the Sharia compliance of cryptocurrencies concerning their structure, transactions, and utility. Secondly, it examines risks associated with price volatility and the stability of investment values. Thirdly, it addresses the ambiguity in regulations and legal frameworks, impacting investor security and protection. Finally, it discusses the integration challenges of Islamic business ethics in the cryptocurrency landscape. The findings underscore that while cryptocurrencies offer potential for lucrative returns, they also entail substantial risks in terms of investor protection from an Islamic business standpoint. Consequently, there is a pressing need for robust regulatory frameworks that align with Sharia principles, alongside enhancing investor awareness and comprehension of cryptocurrency investment risks